A Three-Country Macroeconomic Model for Portugal - Pienkowski, Alex (IMF Working Papers; Working Paper ;, 2019)
This paper outlines a simple three-country macroeconomic model designed to focus on the transmission of external shocks to Portugal. Building on the framework developed by Berg et al (2006), this model differentiates between shocks originating from both inside and outside the euro area, as well as domestic shocks, each of which have different implications for Portugal. This framework is also used to consider the dynamics of the Portuguese economy over recent decades. The model, which is designed to guide forecasts and undertake simulations, can easily be modified for use in other small euro area countries.